2019
DOI: 10.1074/jbc.h118.007210
|View full text |Cite
|
Sign up to set email alerts
|

Sweet and CRISP(R)y parasite engineering

Abstract: Edited by Chris WhitfieldToxoplasma gondii is an intracellular parasite that is highly prevalent within human populations. Its genome encodes a range of enzymes involved in glycan biosynthesis and metabolism. A new study presents a library of CRISPR/Cas9-based glyco-relevant gene knockouts and their examination in glycomic and functional assays. This new resource can pave the way for a better understanding of the role of carbohydrates in infection and immunomodulation by this significant protozoan parasite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It has been shown that carbohydrates and carbohydrate-binding proteins play an essential role in adhesion or invasion of certain parasites into host cells ( 57 ). Furthermore, parasite-derived carbohydrates can trigger the host´s innate and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that carbohydrates and carbohydrate-binding proteins play an essential role in adhesion or invasion of certain parasites into host cells ( 57 ). Furthermore, parasite-derived carbohydrates can trigger the host´s innate and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%